Integrating Construction 4.0 Technologies: A Four-Layer Implementation Plan - El Jazzar, Mahmoud; Schranz, Christian; Urban, Harald; Nassereddine, Hala (Frontiers in Built Environment, 2021)
This research explores the current state of Construction 4.0 and discusses a four-layer implementation of Construction 4.0 in the industry. The research methodology consists of an extensive literature review to gain insights about Construction 4.0 and frame the four-layer implementation plan. A case study is also presented to showcase the proposed implementation plan. Nine Construction 4.0 technologies were discussed, their integration throughout the project lifecycle was presented in a roadmap, their integration and connectivity with one another were outlined in an interaction roadmap, and the requirements necessary for achieving the 4.0 transformation were articulated. However, the proposed implementation plan is focused on nine Construction 4.0 technologies. The research presents a comprehensive plan for integrating Construction 4.0 technologies into the industry and serves as a guideline to help construction companies better understand the implications of Construction 4.0.